Marine Group II Euryarchaeota Contribute to the Archaeal Lipid Pool in Northwestern Pacific Ocean Surface Waters - Ma, Cenling; Coffinet, Sarah; Lipp, Julius S.; Hinrichs, Kai-Uwe; Zhang, Chuanlun (Frontiers in Microbiology, 2020)
Planktonic archaea include predominantly Marine Group I Thaumarchaeota (MG I) and Marine Group II Euryarchaeota (MG II), which play important roles in the oceanic carbon cycle. MG I produce specific lipids called isoprenoid glycerol dibiphytanyl glycerol tetraethers (GDGTs), which are being used in the sea surface temperature proxy named TEX86. Although MG II may be the most abundant planktonic archaeal group in surface water, their lipid composition remains poorly characterized because of the lack of cultured representatives. Circumstantial evidence from previous studies of marine suspended particulate matter suggests that MG II may produce both GDGTs and archaeol-based lipids. In this study, integration of the 16S rRNA gene quantification and sequencing and lipid analysis demonstrated that MG II contributed significantly to the pool of archaeal tetraether lipids in samples collected from MG II-dominated surface waters of the Northwestern Pacific Ocean (NWPO). The archaeal lipid composition in MG II-dominated NWPO waters differed significantly from that of known MG I cultures, containing relatively more 2G-OH-, 2G- and 1G- GDGTs, especially in their acyclic form. Lipid composition in NWPO waters was also markedly different from MG I-dominated surface water samples collected in the East China Sea. GDGTs from MG II-dominated samples seemed to respond to temperature similarly to GDGTs from the MG I-dominated samples, which calls for further study using pure cultures to determine the exact impact of MG II on GDGT-based proxies.